State evaluation of a corroded pipeline. Issue 2 (3rd May 2016) - Wang, Yung-Lien; Li, Chang-Min; Chang, Ren-Rong; Huang, Hung-Ru
ABSTRACT: A submarine pipeline is mainly used to transfer liquid or gas between two land masses and may thus suffer corrosion from the severe subsea environment. Hence, the safety of a corroded pipeline must be evaluated by professionals. In this study, stress analysis of a corroded pipeline is conducted for three situations (i.e. simple defect, complex surface, and interacting defects). A simple defect is modelled using the 3D drawing software CATIA, and ANSYS simulates the stress of the corrosion defect; the effects of the defect were determined using different defect widths and depths. A complex surface involves the use of AUTOCAD VBA to establish the 3D surface based on random data and to generate an Initial Graphics Exchange Specification file. CATIA is used for file opening and geometric modelling and is finally keyed into ANSYS for analysis. ANSYS then is used for the stress analysis. The analysis covers a single rectangular defect, a spherical defect, and interacting effects of both types of defects. Finally, the stress analysis results are explored.